Organic Acid Metabolism and the Impact of Fermentation Practices on Wine Acidity - A Review - Chidi, B.S.; Bauer, F.F.; Rossouw, D. (South African Journal of Enology and Viticulture, 2018)
The conversion of grape sugar to ethanol and carbon dioxide is the primary biochemical reaction in alcoholic wine fermentation, but microbial interactions, as well as complex secondary metabolic reactions, are equally relevant in terms of the composition of the final wine produced. The chemical composition of a wine determines the taste, flavour and aroma of the product, and is determined by many factors such as grape variety, geographical and viticultural conditions, microbial ecology of the grapes and of the fermentation processes, and the winemaking practices. Through the years, major advances have been made in understanding the biochemistry, ecology, physiology and molecular biology of the various yeast strains involved in wine production, and how these yeasts affect wine chemistry and wine sensory properties. However, many important aspects of the impact of yeast on specific wine-relevant sensory parameters remain little understood. One of these areas of limited knowledge is the contribution of individual wine yeast strains to the total organic acid profile of wine. Wine quality is indeed very directly linked to what wine tasters frequently refer to as the sugar–acid balance. The total acidity of a wine is therefore of prime sensory importance, and acidity adjustments are a frequent and legal practice in many wineries. However, the total acidity is the result of the sum of all the individual organic acids that are present in wine. Importantly, each of these acids has its own sensory attributes, with descriptors ranging from fresh to sour to metallic. It is therefore important not only to consider total acidity, but also the contribution of each individual acid to the overall acid profile of the wine. This review will summarise the current knowledge about the origin, synthesis and analysis of organic acids in wine, as well as on the management of wine acidity.